Cu@TiO2 Janus microswimmers with a versatile motion mechanism. Issue 34 (3rd August 2018) - Wang, LinLin; Popescu, Mihail N.; Stavale, Fernando; Ali, Astrid; Gemming, Thomas; Simmchen, Juliane
Abstract : We report novel metal-capped TiO2 photochemically-active colloids endowed with a 'hybrid drive': directional motion is achieved in water upon UV illumination, as well as in dilute peroxide solutions upon illumination with UV or visible light. Abstract : We report novel metal-capped TiO2 photochemically-active colloids endowed with a 'hybrid drive': directional motion is achieved in water upon UV illumination, as well as in dilute peroxide solutions upon illumination with UV or visible light. From the different behaviours of nearby particles, we infer that distinct reaction pathways affect the local composition and flow of the solution.